Intellectual property, design innovation, and entrepreneurship - Hillner, Matthias (Springer, 2021)
This book focuses on intellectual property (IP) in the context of product innovation and design-led start-up management. A distinguished feature is that it analyses innovation-related scenarios within their continuously changing contexts. IP is discussed in relation to the way in which its value changes over time as a venture matures. The book reveals how IP strategies can enhance a start-up’s survival prospects and its growth potential if they are connected systematically to other business development attributes. Being mainly addressed to enterprising designers, it may also support business administration programmes, innovation hubs, design educators, incubator managers, as well as business coaches and IP attorneys who support creatives and inventors. All in all, this book offers a unique and timely strategic guidance in the field of design and innovation management. “Design and design rights have long been overlooked in the plethora of studies on the links between IPR and innovation. Matthias Hillner’s thoughtful and eloquent journey provides a contemporary and meaningful analysis which will no doubt assist governments, economists, academics and designers’ better understanding of design in the context of successful business strategies and IPR. Given design’s significant contribution to global economies, I am confident it will offer much needed guidance.” Dids Macdonald OBE, founder CEO of Anticopying in Design (ACID) "This is an immensely practical book for designers and entrepreneurs who want to understand the issues of IP, product innovation, and business development. With clear explanations, many vivid examples, and strategically useful tips, it will be a valuable resource for creative minds at all levels of experience. A serious book but written with a sensitive touch on how to protect new ideas." Richard Buchanan, Professor of Design, Management, and Innovation, Weatherhead School of Management, Case Western Reserve University.